PREDIKSI EROSI MENGGUNAKAN METODA USLE PADA DAERAH RAWAN GERAKAN TANAH DI DAERAH JALUR LINTAS BENGKULU-KEPAHIANG - Febriani, Yeza (Edu Research, 2013)
Research has been carried out in line-cross Bengkulu-KepahiangKepahiang District in order to determine soil loss prediction caused by erosionproneareas of ground motion using the USLE. The parameters observed in theform of rainfall erosivity (R), soil erodibility (K), slope length (L), slope (S),vegetation factor (C) and the factor of human action in the management of ground(P). The study consisted of 12 sampling locations, processing and analysis of dataconducted in the Laboratory of Soil Science Faculty of Agriculture UNIB. Basedon the analysis of data obtained that the greatest erosion prediction valuecontained in the location 1 is equal to 120.39 tonnes / hectare / year while thevalue of the smallest erosion prediction contained in the site 2 is equal to 2.91tonnes / hectare / year.